Glucose, cholesterol and blood pressure in type II diabetes: A longitudinal observational study comparing patients with and without severe mental illness. Issue 9 (31st July 2019) - Smith, Robert; Han, Lu; Ali, Shehzad; Prady, Stephanie L.; Taylor, Joanne; Hughes, Tom; Ajjan, Ramzi A.; Siddiqi, Najma; Doran, Tim
Accessible Summary: What is known on the subject?: People with severe mental illness (SMI) have a life expectancy of 15–20 years less than the general population, partly due to increased risk of physical disease, including type II diabetes (T2DM) and cardiovascular disease. Little is known about changes in cardiovascular risk factors over time in people with both T2DM and SMI compared to those with T2DM and no SMI. What this paper adds to existing knowledge?: We investigated whether levels of cardiovascular risk factors, cholesterol, HbA1c, systolic and diastolic blood pressure associated with adverse clinical outcomes are different in T2DM patients with and without SMI. We found significant differences in systolic blood pressure and HbA1c between the two groups. Fifty‐five percent and twenty‐nine percent of T2DM patients with comorbid SMI are at increased risk of adverse clinical outcomes due to sub‐optimal HbA1c and systolic blood pressure levels, respectively. What are the implications for practice?: Many patients with T2DM and SMI have higher levels of cardiovascular risk compared to patients with T2DM only, and good management of risk factors is therefore particularly important in patients with both conditions. Achieving better control of HbA1c levels is likely to be central to addressing inequalities in outcomes for patients with both SMI and T2DM. Abstract: Introduction: Patients with both severe mental illness (SMI) and type II diabetes (T2DM) have lower life expectancy than patients with T2DM alone, partly due to poor control of cardiovascular risk factors in comorbid patients. Aim: To compare levels of cholesterol, HbA1c and blood pressure in T2DM patients with and without SMI. Method: We analysed longitudinal clinical records of 30, 353 people with T2DM (657 with SMI; 29, 696 controls without SMI) between 2001 and 2013 using the Clinical Practice Research Datalink (CPRD). We used mixed‐effects regression models to compare cardiovascular risk factors between SMI and controls. Results: Patients with SMI had lower mean systolic blood pressure (SBP; β : −2.49; SE = .45 p = <.01) and were more likely to have extreme (high and low) values of HbA1c and SBP (OR: 1.38, 95% CI: 1.16, 1.64 and 1.76:1.40, 2.21, respectively). Discussion: People with T2DM and SMI have similar average values of cardiovascular risk factors to people with T2DM alone but are more likely to have values of HbA1c and SBP indicating increased risk of adverse clinical outcomes. Implications for Practice: Improved management of cardiovascular risk factors in general, glycaemic control in particular, is central to addressing the increased risk of adverse outcomes in people with both SMI and T2DM.